The cumacean Genus Eudorella (Crustacea: Peracarida) from Japanese Waters, Northwest Pacific, and E. suluensis sp. nov. from the Sulu Sea, Indo-West Pacific - Akiyama, Tadashi; Gamô, Sigeo (Zootaxa, 2012)
Cumacean crustaceans in the genus Eudorella (Leuconidae) from Japanese waters, in the Northwest Pacific, were examinedand the following 15 species were recognized: E. acuticaudata sp. nov.; E. æquiremis Hansen, 1920; E. bathyalis Vassilenko &Tzareva, 2004; E. bathyhwanghaensis sp. nov.; E. breviflagella sp. nov.; E. dentata Lomakina, 1955; E. emarginata (Kroer,1846); E. fusafusa sp. nov.; E. haradai sp. nov.; E. hwanghaensis Hong & Park, 1999; E. ohtai sp. nov.; E. orientalis sp. nov.;E. parahirsuta sp. nov.; E. ryukyuensis Akiyama & Gamô, 2005; and E. setoensis Akiyama & Gamô, 2006. In addition,Eudorella suluensis sp. nov., was collected from the Sulu Sea, Philippines, Indo-West Pacific, 688–693 m. These speciesinclude 2 groups on the basis of shared morphological characters. Eudorella bathyalis, E. breviflagella sp. nov., E. fusafusa, E.orientalis, and E. setoensis are characterized by a row of simple setae on each side of the carapace, with both E. breviflagellaand E, setoensis also characterized by a short flagellum on antenna 2 in adult males. The other group consists of Eudorellahwanghaensis, E. bathyhwanghaensis, and E. ryukyuensis, from southern Japan, and E. suluensis; with E. hwanghaensis and E. bathyhwanghaensis also characterized by a peculiar secondary sexual character on the tip of the 3rd pereopod in adult males.